Variables Affecting Willingness to Communicate in English among Vietnamese College Students - Nguyen, Manh Hoai (2016)
Seeking opportunities to communicate greatly increases the chances for intercultural contact, as well as L2 communication practice with comprehensible input when learning a second or foreign language. The communicative language teaching approach has focused on students’ individual differences as English learners and users while highly emphasizing the importance of communicative language teaching for the development of students’ communication competence in the classroom. However, despite the emphasis on communication and the view broadly accepted both by educators and learners that L2 learners need practice speaking so that they can communicate, students in the Vietnamese context appear to choose to remain silent when there are opportunities to use English. It needs to be examined if learners would communicate in English when they had chances, and what factors would affect their willingness to communicate. The present study was conducted at three colleges in Vietnam. The study attempted to examine Vietnamese EFL students’ perceptions of willingness to communicate (WTC) in English and other individual variables related to English communication and to investigate the relationships among these English learning and communication variables. The study used a design that combined both quantitative and qualitative data collection and analysis procedures. Questionnaires were first collected from 500 undergraduate students. Then, interviews were conducted with 20 students who had already answered the questionnaires. Structural equation model (SEM) analysis was used to examine the relationships among WTC in English, Self-perceived Communication Competence (SPCC) and Communication Apprehension (CA), Motivation, Attitudes, and Personality. Qualitative interviews were conducted to extend and elaborate on the quantitative results. The results showed that students had low WTC, low SPCC, moderate CA, moderate motivation, somewhat negative attitudes, and moderate personality in terms of introversion-extraversion personality traits. The path model proposed in the present study showed that the variables that directly influenced WTC in English were Self-perceived Communication Competence (SPCC), Motivation, Attitudes, and Personality. Generally, the model suggested in the present study provided support to Gardner’s SLA model and MacIntyre et al.’s heuristic model. Based on these findings, pedagogical implications for English teaching and learning were suggested to increase willingness to communicate.